Women with Carpal Tunnel Syndrome Caused by being Overweight and Her Occupation as a Tailor - Jawaharlal Akbar Lalchanzani; Rita Rosita (Jurnal Ilmu Kedokteran Keluarga, 2022)
Carpal Tunnel Syndrome (CTS) is a neuropathic entrapment due to compression of the median nerve that passes through the carpal tunnel at the wrist. The most common etiology of CTS is a history of repetitive wrist movements such as sewing. This case report discusses the diagnosis and management of CTS using a family medicine approach. Abstrak Carpal Tunnel Syndrome (CTS) merupakan jeratan neuropati akibat kompresi pada nervus medianus yang melewati carpal tunnel di pergelangan tangan. Etiologi paling sering pada CTS yaitu riwayat gerakan pergelangan tangan yang bersifat repetitif seperti menjahit. Laporan kasus ini membahas diagnosis dan tatalaksana CTS secara menyeluruh dengan pendekatan ilmu kedokteran keluarga. Kata Kunci: Carpal Tunnel Syndrome, neuropathic entrapment, kedokteran keluarga, biopsikososial Dimensions Index : https://app.dimensions.ai/details/publication/pub.1154332708